Farming on the Fringe: Diachronic Changes in Land-Use Patterns and Agricultural Strategies in Ancient Nemea - Cloke, Christian F. (Journal of Greek Archaeology, 2021)
Between 1984 and 1990, the Nemea Valley Archaeological Project (hereafter NVAP), systematically surveyed the Nemea, Asopos, and Longopotamos Valleys, around Nemea, Phlious, and Kleonai in the northeastern Peloponnesos (Figure 1). This survey, covering an area of roughly 80 square kilometers, was for its time cutting-edge, both in its intensive approach to surveying the totality of the walkable landscape, and its use of computers for recording and mapping finds. The fieldwalking and record-keeping methods employed, which treated individual artifacts as the basic units of analysis, have produced a robust dataset for evaluating settlement patterns, agricultural land-use, and other past human activities within their ecological, economic, social, and historical contexts. This chapter examines the NVAP survey territory and considers the contributions of intensive pedestrian survey to the crafting of a medium- to long-term history of the Greek countryside from the Archaic to Late Roman periods. Through detailed analyses of survey finds’ physical properties and spatial distribution, I assess past settlement patterns and agricultural methods, consider the dynamics of regional production and consumption of ceramics and other goods, and elucidate a range of activities carried out at rural sites.